BRAND PERSONALITY AND CONSUMER SATISFACTION FROM GUINNESS IN CAMEROON: TWO MEASURES BY ONE CONSTRUCT, EMOTION AND GRATIFICATION - ABBA PATOU, Moise; TCHINGNABE, Daniel (Revue Internationale des Sciences de Gestion, 2024)
Nowadays, brands are a very important part of our society. They are only multiplying, thereby creating general confusion in the minds of consumers, which forces companies to seek a differentiated positioning on the market. This study aims to analyze the explanatory power of brand personality on consumer satisfaction through emotion and gratification. Using a quantitative approach, a survey conducted among a large sample of consumers of the Guinness brand in Cameroon made it possible to test and verify the various research hypotheses using regression analyses. Thus, the result obtained highlights the direct influence of brand personality on satisfaction as well as its predictive power on consumer emotion and gratification. However, it highlights the interest for managers to take into consideration the concept of brand personality in the management of their brands.